(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the semantic classification of phraseological units in English and Uzbek languages, with special attention given to idioms containing animal names. The study reveals both universal and culturally specific aspects in the way phraseological meaning is constructed and interpreted across the two languages. It provides a structured overview of major semantic types of phraseological units, analyzes examples, and examines the cultural, cognitive, and linguistic factors that influence their classification. The research demonstrates how phraseological semantics reflects national mentality, worldview, and linguistic creativity.